Zmiany w zasobach gospodarstw o zróżnicowanym wykorzystaniu najemnej siły roboczej - Klepacki, Bogdan (Changes in Farm Resources with Differentiated Use of Hired Labour Force, 2005)
In the paper the change of resource level in farm with own and hired labor has been presented. The author states that farms with permanent hired labor are the biggest and grow very fast. In these farms the number of animals was the highest. The same we can say about the income level. Generally it can be stated that farms with permanent hired labor is more economical more stronger and presents better dynamic development in comparison with farms without hired labor.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 431-436